Deep packet inspection oriented high speed packet parsing architecture - Yong-ji DONG; Yun-fei GUO; Wan-wei HUANG; Hui-qun HUANG (Tongxin xuebao)
A deep packet inspection oriented high speed packet parsing architecture called BiPPCS (bidirectional packet parsing architecture for content security) was proposed. Firstly, the content extraction tree was used to describe the cou-pling of the protocol relationship to improve flexibility of the packet parsing. Secondly, hardware bi-directional parallel pipeline was used to enhance the processing rate of the packet parsing. Thirdly, a node mapping algorithm was used to balance the number of nodes on all pipeline stages to optimize the storage space. Analysis and simulation show that BiPPCS gets balance among the rate processing, resource consumption and other aspects.